Bioresorbable High-Strength HA/PLLA Composites for Internal Fracture Fixation - Jie Liu; Mingtao Sun; Yipeng He; Weixia Yan; Muhuo Yu; Keqing Han (Molecules)
In modern surgery, the internal fixation plates fabricated from hydroxyapatite/poly(L-lactide) (HA/PLLA) composites encounter clinical limitations in fracture treatment due to their inadequate mechanical properties. In this work, pressure-induced flow (PIF) technique is employed to address this limitation. Under optimal processing conditions (140 °C and 250 MPa), the HA/PLLA composites exhibit an impressive flexural strength of 199.2 MPa, which is comparable to that of human cortical bone, the strongest bone tissue in the body. The tensile strength and the notched Izod impact strength are close to 84.2 MPa and 16.7 kJ/m2, respectively. Meanwhile, the HA/PLLA composites develop multi-level stacked crystal layers during PIF processing, accompanied by increases in crystallinity (53.1%), crystal orientation (81.6%) and glass transition temperature (78.8 °C). After 2 months of in vitro degradation, the HA/PLLA composites processed by the PIF technique still maintain considerable flexural strength (135.3 MPa). The excellent mechanical properties of HA/PLLA composites processed by PIF technique expand their potential as an internal fixation plate.